Stabilisasi Ekonomi dalam Penyerapan Tenaga Kerja - Wiwik Damayanti (CV. Creative Tugu Pena, 2024)
The influence of workers' education levels and the influence of economic growth on economic stabilization affect environmental welfare, this is inseparable from the contribution of the right labor absorption so that it can create more jobs. This study aims to find out how the level of education and labor absorption affects the economic stabilization of the environment. This research is a descriptive qualitative research. The data used is BPS (Central Statistics Agency) data of East Lampung Regency. The analysis technique in this study is interview and observation of BPS (Central Statistics Agency) data of East Lampung Regency. The results of the research on the absorption of labor with different levels of education turned out to affect environmental stability, this showed a strong foundation and appropriate services increased purchasing power and bargaining power more significantly.